SCHOOL-BASED EYE CARE PROGRAM IN YOGYAKARTA: EDUCATION, BASIC EYE EXAMINATION, AND DIGITAL MEDIA ENGAGEMENT AT STELLA DUCE 2 SENIOR HIGH SCHOOL - Priskila, Loury; Yeckopradana, Ebenezer Devara; Sasabone, Ahava Tasa; Cahyani, Ni Kade Dian Ary (Universitas Jambi, 2025)
This community service program aimed to increase awareness of eye health and facilitate early detection of refractive errors among students at Stella Duce 2 Senior High School, Yogyakarta. The activities were conducted from August 4-8, 2025, involving Grade X students as the main participants, with teachers and staff as additional targets. The methods included interactive health education, basic eye examinations (visual acuity, ocular motility, color vision, pupillary reflex, external and internal checks), and a short video competition themed “Jaga Mata untuk Masa Depan Cerah.” Results showed active student participation in education sessions, 190 individuals underwent eye screening, and several refractive errors requiring correction or referral were detected. The video competition produced creative educational content that was shared on social media, extending the program’s outreach. In conclusion, the program improved eye health awareness, enabled early detection of vision problems, and encouraged digital health promotion. This model can be replicated in other schools to strengthen promotive and preventive eye care.